A male torso (headless) standing figure with an attendant on the right - Temples of India Project Team (Jio Institute, 2024)
A few loose sculptures can be seen inside the temple complex. One such sculpture shows a male torso (headless) standing, bejewelled, holding an object which looks like a staff. There is an attendant next (right) to it, which is shown as small in stature, with one arm raised up.